If Artificial Superintelligence Were to Cause Our Extinction, Would That Be So Bad? - Torres, Émile (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
This article examines whether human extinction brought about by a “value-misaligned” artificial superintelligence (ASI) would be bad, and for what reasons. The question, I contend, is deceptively complex. I proceed by outlining the three main positions within Existential Ethics, i.e., the study of the ethical and evaluative implications of human extinction. These are equivalence views, further-loss views, and pro-extinctionist views. I then show how exponents of each view would evaluate a scenario in which humanity goes extinct due to ASI. Although there are some points of agreement, these three positions diverge in significant ways, most of which have not been adequately explored in the philosophical literature.